Implementasi Media Pembelajaran (PUGAWA) Untuk Meningkatkan Minat Belajar Bahasa Indonesia Siswa Kelas VII SMPN 2 Jenangan Ponorogo - Shaila Rahma Anggraini; Fauzatul Ma’rufah Rohmanurmeta; Sri Bintarti (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
The education system, which is actually used to improve students' abilities to be more active and proficient in learning, is often considered inappropriate and not in accordance with the real situation at school. Students who tend to be shy and passive will not ask or learn on their own what is ordered by the teacher. In addition, lessons that are considered difficult and boring will make students less interested in learning these lessons. One effort to change students' attitudes in learning Indonesian is to use interactive and non-monotonous learning media. Learning media "Pungawa" is one of the media that can be applied in learning Indonesian. This media is media that uses three-colored ballpoint pens in the search to make it look interesting and fun. In this lesson students can use a ballpoint pen with three types of ink colors used to summarize a learning material. The results of the research on the implementation of "pugawa" learning media to increase interest in learning Indonesian for class VII students of SMPN 2 Jenangan Ponorogo show that the use of retainer learning media in the teaching and learning process of Indonesian subjects is stated to be in accordance with the objectives, namely students become more understanding and interested in the learning process which is conducted. Keyword: Education; Learning media; Retainer.